Synthesis of porous Au–Ag alloy nanorods with tunable plasmonic properties and intrinsic hotspots for surface-enhanced Raman scattering. Issue 19 (26th April 2021) - Ke, Shanlin; Kan, Caixia; Zhu, Xingzhong; Wang, Changshun; Wang, Xiu; Chen, Yuan; Zhu, Xiaoguang; Li, Zhaosheng; Shi, Daning
Abstract : The tunability of longitudinal plasmonic bands of P-AuAgNRs is realized to cover a wide range of wavelengths. P-AuAgNRs exhibit numerous internal hotspots which favor highly sensitive surface-enhanced Raman scattering detection. Abstract : Plasmonic nanostructures exhibiting interior nanopores have found increasing applications in the fields of sensors and surface-enhanced Raman scattering due to controllable optical properties and built-in hotspots. Nonetheless, precise control over density of the nanopores in three-dimensional nanostructures remains a great challenge. In this study, we propose an effective synthesis strategy for porous Au–Ag alloy nanorods (P-AuAgNRs) by dealloying of Ag atoms from solid Au–Ag alloy nanorods in the presence of Fe(NO3 )3 . The strategy produced P-AuAgNRs with various degrees of porosity, which demonstrated a facile plasmonic tunability across visible to near-IR regions (indicated by longitudinal surface plasmon resonance peaks). Furthermore, experimental observations and theoretical finite-difference time-domain simulations indicated that P-AuAgNRs exhibit numerous internal hotspots which favor highly sensitive surface-enhanced Raman scattering (SERS) detection for rhodamine 6G and 4-nitrothiophenol. The enhanced SERS performance was remarkably maintained under oxidative environments. Overall, we demonstrated the reliability of the proposed strategy for synthesizing P-AuAgNRs with controlled nanopores and internal hotspots. Thus, we recommend the adoption of this strategy for the preparation of other porous nanoparticles exhibiting intrinsic hotspots for SERS-based analytical sensors and imaging application.